Strike zone - Lupica, Mike (Puffin Books, 2020)
Twelve-year-old pitcher Nick Garcia dreams of winning the Little League MVP and throwing out the first pitch at Yankee Stadium. But he also dreams of a world where his sister can be cured of lupus and his undocumented parents don't have to live in fear of the government. Then his worst fears come to pass and they affect his fastball. Fortunately, an unlikely hero steps in just in time.